Surgical technique for repair of complex anterior skull base defects - Reinard, Kevin (Surg Neurol Int, 2015)
BACKGROUND: Modern microsurgical techniques enable en bloc resection of complex skull base tumors. Anterior cranial base surgery, particularly, has been associated with a high rate of postoperative cerebrospinal fluid (CSF) leak, meningitis, intracranial abscess, and pneumocephalus. We introduce simple modifications to already existing surgical strategies designed to minimize the incidence of postoperative CSF leak and associated morbidity and mortality. METHODS: Medical records from 1995 to 2013 were reviewed in accordance with the Institutional Review Board. We identified 21 patients who underwent operations for repair of large anterior skull base defects following removal of sinonasal or intracranial pathology using standard craniofacial procedures. Patient charts were screened for CSF leak, meningitis, or intracranial abscess formation. RESULTS: A total of 15 male and 6 female patients with an age range of 26–89 years were included. All patients were managed with the same operative technique for reconstruction of the frontal dura and skull base defect. Spinal drainage was used intraoperatively in all cases but the lumbar drain was removed at the end of each case in all patients. Only one patient required re-operation for repair of persistent CSF leak. None of the patients developed meningitis or intracranial abscess. There were no perioperative mortalities. Median follow-up was 10 months. CONCLUSION: The layered reconstruction of large anterior cranial fossa defects resulted in postoperative CSF leak in only 5% of the patients and represents a simple and effective closure option for skull base surgeons.